オングルトウ オヨビ ソノ シュウヘン チイキ ノ センルイ ヨホウ - 堀川, 芳雄; ホリカワ, ヨシオ; HORIKAWA, Yoshio (国立極地研究所, 1961)
P(論文) This report is based on the collections made by S. NAKANO, T. KAJI, S. SAIKI (1957) and by H. FUKUSHIMA (1959) in Ongul Island (69°S, 39°E) and its nearest areas of the Antarctic Continent. The collections include the following four mosses (all sterile). 1. Ceratodon purpureus (Hedw.) Brid. Judging from the fact that it comprises the greater part of the collections, this species seems to be more dominant in the area explored. It is noteworthy that the specimens observed exhibit extraordinary diversity in the leaf characteristics: the shape of the acumen, the nature of the margin whether revolute or plane, the size of the leaf cells and the thickness of the cell-wall. The plants grow in very compact tufts, forming larger or smaller cushion-like colonies. 2. Bryum argenteum Hedw. This worldwide moss seems to be frequent in the Antarctic region as well. The specimens observed showed the leaves which were obtuse in apices and had costa sometims ending below the apex. 3. Bryum sp. (A) This is near or may be referred to Bryum inconnexum Card, or Webera Racovitzae Card., both of which were described from Gerlache, but the final determination is reserved until the original specimens of those species are actually seen. 4. Bryum sp. (B) Considerable numbers of species belonging to the genus Bryum have so far been recorded from the Antarctic region, but most of them are difficult to recognize because they seem to be very variable and the original description represents only one case of the variation. However, this material is distinct and seems to be a new species. Further study is expected. departmental bulletin paper